Loss of superfluidity in a Bose-Einstein condensate on an optical lattice via a novel classical phase transition - Adhikari, S. K. (Elsevier B.V., 2003)
We predict the loss of superfluidity in a Bose-Einstein condensate (BEC) trapped in a combined optical and axially-symmetric harmonic potentials during a resonant collective excitation initiated by a periodic modulation of the atomic scattering length a, when the modulation frequency equals twice the radial trapping frequency or multiples thereof. This classical dynamical transition is marked by a loss of superfluidity in the BEC and a subsequent destruction of the interference pattern upon free expansion. Suggestion for future experiment is made. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: Bose-Einstein condensation; superfluid-insulator transition